Multisite Veno-Venous Cannulation for Neonates and Nonambulatory Children*. Issue 8 (5th May 2021) - Lillie, Jon; Pienaar, Alison; Budd, Jenny; Speggiorin, Simone; Gordon, Anne; James, Paul; Perkins, Jo; Griffiths, Benedict; Fine-Goulden, Miriam; Austin, Conal; Salih, Caner; Agnew, Nicola; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : OBJECTIVES: Neonates with respiratory failure are ideally supported with veno-venous rather than veno-arterial extracorporeal membrane oxygenation due to the reduced rate of neurologic complications. However, the proportion of neonates supported with veno-venous extracorporeal membrane oxygenation is declining. We report multisite veno-venous extracorporeal membrane oxygenation, accessing the neck, returning to the inferior vena cava via the common femoral vein in neonates and children less than 10 kg. DESIGN: Retrospective case series with 1 year minimum follow-up. PATIENTS: Patients less than 10 kg supported with veno-venous extracorporeal membrane oxygenation accessing the jugular and returning to the femoral vein SETTING: A 30-bed pediatric intensive care delivering extracorporeal membrane oxygenation to approximately 20 children annually. INTERVENTIONS: Veno-venous extracorporeal membrane oxygenation accessing the jugular and returning to the femoral vein was delivered using two single lumen cannulae. MEASUREMENTS AND MAIN RESULTS: January 2015 to August 2019, 11 patients underwent veno-venous extracorporeal membrane oxygenation accessing the jugular and returning to the femoral vein with median weight of 3.6 kg (interquartile range 2.8–6.1 kg), and median corrected gestational age of 13 days (interquartile range, 2–175 d). The smallest patient weighed 2.1 kg. Seven patients had comorbidities. Extracorporeal membrane oxygenation was technically successful in all patients with median flows of 126 mL/kg/min (interquartile range, 120–138 mL/kg/min) and median arterial oxygenation saturation of 94% (interquartile range, 91–98%) at 24 hours. Nine survived to home discharge, and two were palliated. Common femoral vein occlusion was observed in all patients on ultrasound post decannulation. There was no clinical or functional deficit in the cannulated limb at follow-up, a minimum of 1 year post extracorporeal membrane oxygenation. CONCLUSIONS: Veno-venous extracorporeal membrane oxygenation accessing the jugular and returning to the femoral vein was performed safely in patients under 10 kg with the smallest patient weighing 2.1 kg. Although occlusion of the common femoral vein was observed in patients post decannulation, subsequent follow-up demonstrated no clinical implications. We challenge current practice that veno-venous extracorporeal membrane oxygenation accessing the jugular and returning to the femoral vein cannot be performed in nonambulatory patients and suggest that this strategy is preferred over veno-arterial extracorporeal membrane oxygenation in infants requiring extracorporeal membrane oxygenation for respiratory failure.